Evaluation of the anti-cancer potential of Mahonia aquifolium extracts via apoptosis and anti-angiogenesis - Ana Damjanovic Damjanovic; Gordana Zdunic; Katarina Savikin; Boris Mandic; Milka Jadranin; Ivana Z. Matic; Tatjana P. Stanojkovic (Bangladesh Pharmacological Society, 2016)
The cytotoxicity of Mahonia aquifolium ethanol and water extracts was examined using MTT test. The morphological changes were analyzed by fluorescence microscopy. Cell cycle distribution and possible activation of caspase-dependent pathway of cell death were assessed by flow cytometry. The effects of ethanol and water extracts on migration of endothelial EA.hy926 cells were analyzed by in vitro scratch assay and inhibition of angiogenesis was detected using tube formation assay. Both extracts demonstrated cytotoxic effects on cancer cell lines with very high selectivity. Morphological evaluation indicated apoptosis. These results were confirmed with cell cycle analysis, where there was accumulation of cancer cells in the subG1 phase. Ethanol and water extracts induced a caspase-dependent apoptosis in HeLa cells through activation of caspase-3 and caspase-8. Both extracts showed the ability to inbibit the migration of EA.hy926 cells and initial steps of angiogenesis. In addition, ethanol extract exerted significant anti-angiogenic effect. Video Clips of Methodology: Cell seeding: 2 min 26 sec   Full Screen   Alternate 4 hours after treatment of MTT-SDS applied: 54 sec   Full Screen   Alternate 72 hours after treatment MTT applied: 1 min 8 sec   Full Screen   Alternate Day 2 treatment: 1 min 32 sec   Full Screen   Alternate Measuring absorbance: 9 sec   Full Screen   Alternate